DEVELOPMENT OF PUBLIC-PRIVATE PARTNERSHIPS IN THE AGRARIAN SECTOR OF UKRAINE: INSTITUTIONAL ASPECT - Igor L. Fedun, Yuliia І. Holovnia, Olha V. Diachenko, Maryna G. Slokva, Nadiia P. Reznik (International Journal of Advanced Science and Technology, 2020)
Article systematize and summarize key conceptual approaches to the formation of the public-private partnership institute in the context of increasing innovation and investment support for the development of the agrarian sector of the Ukrainian economy. The world experience of formation and development of state-private partnership models and their features is investigated. The monitoring of threats and challenges related to the formation of perspective vectors of cooperation between business and state in the conditions of decentralization of power is monitored. The institutional structure and basic models of the development of the public-private partnership institution, which includes the mechanism of implementation in the agrarian sector of the national economy of Ukraine, is formed.